Examining Dividend Policy's Impact on Stock Returns with Profitability and Liquidity Analysis - Putra, I Gede Cahyadi; Apriada, Kadek; Bagiana, I Kadek (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2024)
The aim of this research is to address the lack of existing literature on the correlation between dividend policy and stock performance in the banking industry. This paper examines the intervention mechanisms that mediate the relationship between dividend policy and stock returns, with a specific focus on profitability and liquidity as determining factors. According to the research findings, profitability has a notable positive impact on dividend policy, whereas liquidity has a significant negative impact. Nevertheless, both profitability and liquidity do not directly impact stock returns. Dividend policy does not directly impact stock returns. These data suggest that the link between these factors is not linear, and the dividend policy variable does not operate as a mediator for the impact of profitability or liquidity on stock returns. These findings suggest that it is important to consider other factors that may affect the relationship between dividend policy and stock returns. Additionally, it highlights the significance of utilizing diverse and knowledge-based investment strategies to maximize shareholder value in the context of the capital market.